Indicators of dementia disease progression in primary care: An electronic health record cohort study. (21st January 2021) - Rathod‐Mistry, Trishna; Marshall, Michelle; Campbell, Paul; Bailey, James; Chew‐Graham, Carolyn A.; Croft, Peter; Frisher, Martin; Hayward, Richard; Negi, Rashi; Robinson, Louise; Singh, Swaran; Sumathipala, Athula; et al.
Abstract: Background and purpose: The objectives were to assess the feasibility and validity of using markers of dementia‐related health as indicators of dementia progression in primary care, by assessing the frequency with which they are recorded and by testing the hypothesis that they are associated with recognised outcomes of dementia. The markers, in 13 domains, were derived previously through literature review, expert consensus, and analysis of regional primary care records. Methods: The study population consisted of patients with a recorded dementia diagnosis in the Clinical Practice Research Datalink, a UK primary care database linked to secondary care records. Incidence of recorded domains in the 36 months after diagnosis was determined. Associations of recording of domains with future hospital admission, palliative care, and mortality were derived. Results: There were 30, 463 people with diagnosed dementia. Incidence of domains ranged from 469/1000 person‐years (Increased Multimorbidity) to 11/1000 (Home Pressures). An increasing number of domains in which a new marker was recorded in the first year after diagnosis was associated with hospital admission (hazard ratio for ≥4 domains vs. no domains = 1.24; 95% confidence interval = 1.15–1.33), palliative care (1.87; 1.62–2.15), and mortality (1.57; 1.47–1.67). Individual domains were associated with outcomes with varying strengths of association. Conclusions: Feasibility and validity of potential indicators of progression of dementia derived from primary care records are supported by their frequency of recording and associations with recognised outcomes. Further research should assess whether these markers can help identify patients with poorer prognosis to improve outcomes through stratified care and targeted support. Abstract : This study examined the feasibility and validity of using information recorded in primary care records as indicators of dementia progression. The indicators were nested in 13 domains, and having a higher number of newly recorded domains was associated with recognised outcomes (hospital admission, palliative care, mortality). These indicators may help identify patients with poorer prognosis in order to improve outcomes through stratified care and targeted support.